Data Collection to Fulfil the Targets for the SDGs: The APIK Gender Justice Index (AGJI) - Saskia Wieringa (Yayasan Jurnal Perempuan, 2019)
Indonesia has committed itself to the 2030 Agenda with 17 Sustainable Development Goals (SDGs) which were approved by the United Nations on September 25, 2015. Seventeen objectives and 169 related targets must be achieved by 2030. Gender equality is an independent goal (SDG number 5), but gender related issues are also contained in the goal of poverty alleviation (SDG 1), health care including maternal and child health (SDG 3) and education (SDG 4). SDG number 16 concerns a commitment to peace, access to justice and strong institutions. Reliable and inclusive gender statistics are needed to monitor progress towards achieving gender equality and justice and to identify key gender inequalities that require policy interventions. Both quantitative and qualitative data are needed. In addition, certain problems are specific for women, such as maternal death. Given the wide diversity in gender relations and socio-economic conditions of the Indonesian archipelago subnational data are required. This article outlines the methodology of designing the APIK Gender Justice Index. The main findings are that the availability of sex-disaggregated data at the subnational level leaves much to be desired. The AGJI proves to be a reliable, comprehensive and flexible tool that can easily be used by policy makers and activists to design policies and programs to address gender-based discrimination in Indonesia, for instance in the field of health. The AGJI is based on locally available data. The advantages of the AGJI are that it can be computed with a minimum of cost and effort to achieve a maximum of reliability and ease in use. The GSI was found to be comparable with the Global Gender Gap Index (GGGI) for Indonesia but it is more sensitive to political empowerment. The AGJI assesses in how far women have been able to take up leadership positions at subnational levels, including at the village level and are represented in the major decision-making bodies such as the judiciary.